Flow investigation of a miniature pulsatile pump - Koh, Tee Yan. (2013)
Fluid flow pattern for a miniature pulsatile pump is investigated through experimental flow visualization method conducted through the use of an existing in house experimental rig. The original experimental rig is modified in this project to further enhance the quality of the images captured. Various imaging methods are also used to determine the best method of capturing the require image. To ensure consistency, the pump was set to run at 100 rpm for the capturing of all images.